Improving total sediment load prediction using genetic programming technique (Case Study: Malaysia) - N. A., Ahmad Abdul Ghani; N. A., Kamal; J., Ariffin (Institute of Physics Publishing, 2020)
Predicted total sediment load is usually used to identify the intensity of a sedimentation process. Currently, the existing available models to predict total load are mostly developed based on data collected from flumes, channels and rivers located in western countries. These models known as sediment transport model may not be valid to predict total sediment load of rivers in the tropics due to significant differences in the hydrological and sediment characteristics conditions. A new technique called Genetic programming (GP) technique is used to develop a new model to improve the prediction of total sediment load for rivers in tropical Malaysia. The new model named Evolutionary Polynomial Regression (EPR) model is compared with other three available sediment transport models using the different techniques including, Regression Equation, Modified Graf and Multiple Regression. Statistical analyses based on 82 data sets show the sediment transport model using this new technique perform well compare to other models.